Bone Morphogenetic Protein‐2 Promotes Human Mesenchymal Stem Cell Survival and Resultant Bone Formation When Entrapped in Photocrosslinked Alginate Hydrogels. Issue 19 (1st September 2016) - Ho, Steve S.; Vollmer, Nina L.; Refaat, Motasem I.; Jeon, Oju; Alsberg, Eben; Lee, Mark A.; Leach, J. Kent
Abstract : There is a substantial need to prolong cell persistence and enhance functionality in situ to enhance cell‐based tissue repair. Bone morphogenetic protein‐2 (BMP‐2) is often used at high concentrations for osteogenic differentiation of mesenchymal stem cells (MSCs) but can induce apoptosis. Biomaterials facilitate the delivery of lower doses of BMP‐2, reducing side effects and localizing materials at target sites. Photocrosslinked alginate hydrogels (PAHs) can deliver osteogenic materials to irregular‐sized bone defects, providing improved control over material degradation compared to ionically cross‐linked hydrogels. It is hypothesized that the delivery of MSCs and BMP‐2 from a PAH increases cell persistence by reducing apoptosis, while promoting osteogenic differentiation and enhancing bone formation compared to MSCs in PAHs without BMP‐2. BMP‐2 significantly decreases apoptosis and enhances survival of photoencapsulated MSCs, while simultaneously promoting osteogenic differentiation in vitro. Bioluminescence imaging reveals increased MSC survival when implanted in BMP‐2 PAHs. Bone defects treated with MSCs in BMP‐2 PAHs demonstrate 100% union as early as 8 weeks and significantly higher bone volumes at 12 weeks, while defects with MSC‐entrapped PAHs alone do not fully bridge. This study demonstrates that transplantation of MSCs with BMP‐2 in PAHs achieves robust bone healing, providing a promising platform for bone repair. Abstract : Bone morphogenetic protein‐2 (BMP‐2), a potent osteoinductive factor, inhibits apoptosis and promotes survival and osteogenesis of human mesenchymal stem cells (MSCs) when entrapped in a photocrosslinkable alginate hydrogel.